Migration and Remittances : Eastern Europe and the Former Soviet Union - Mansoor, Ali (Washington, DC: World Bank, 2012)
In regard to migration and remittances for Eastern Europe and the Former Soviet Union, the overview chapter summarizes the main findings that are developed in much greater detail in later chapters. The core focus of this report is on documenting the trends of international migration and remittances in this region since the period of transition (chapters one and two) and discussing the determinants of migration in this region (chapter three). A final chapter (chapter four) reviews the organization of international migration policy in the region. It details the nature and types of bilateral migration schemes in place between Europe and Central Asia (ECA) countries and between ECA and Western Europe and identifies some of their limitations. The final section of chapter four suggests some avenues through which bilateral migration agreements could be improved.